Symmetry-Broken Solitons in Photonic Molecules - Ghosh, Alekhya; Pal, Arghadeep; Hill, Lewis; Yan, Haochen; Del'haye, Pascal (2025 Conference on Lasers and Electro-Optics, CLEO 2025, 2025)
We investigate spontaneous symmetry breaking of light fields in coupled resonators. Our study shows symmetry broken soliton states in two-resonator systems. This can be used for on-chip light distribution in telecom systems and optical computing.
CRIS-Team Scopus Importer:2025-11-21